Functional and antiglycation properties of cow milk set yogurt enriched with Nyctanthes arbor-tristis L. flower extract - Amadarshanie, D.B.T.; Gunathilaka, T.L.; Silva, R. M.; Navaratne, S.B. (Elsevier Ltd., 2022)
The fortification of yogurt with natural herbs to improve its nutritional and health benefit are an emerging trend. Hot infusions of Nyctanthes abo-tristis flowers are a traditionally used herb against diabetes. This study was designed to develop a novel yogurt fortified (FY) with 3, 3.5, and 6% N.arbor-tristis flower extract (NFE) to determine its suitability as a fortifier en route to innovative functional products. Upon fermentation, the highest sensory scores were obtained for the 3.5% NFE-FY with 11-, 6-, 3-fold higher antiglycation (NFE- IC50: 28.04 ± 1.13 μg/mL and 3.5% NFE-FY IC50: 46.80 ± 0.92 μg/mL) activity, free radical scavenging potentials, and total phenolic content, respectively. An improvement of texture profile values was observed in 3.5% NFE-FY compared to the control with 3.00 ± 0.1% fat, 3.88 ± 0.23% crude protein, 77.94 ± 0.09 moisture, 14.97 ± 0.27 total soluble solids, and 0.7637 ± 0.03 ash. The 3.5%NEF-FY also exhibited a longer shelf life and less microbial growth than the control. The GC-MS analysis of the NFE indicated the presence of phytochemicals essential for the observed bioactivity. The results confirmed that the N.arbor-tristis flower extract increased the overall quality of the yogurt and tested bioactivity. NFE-FY could be used in yogurt production to optimize the health benefits with improved functional characteristics to prevent diet-driven glycation activity.
Keywords: Antioxidant properties N. arbor-tristis flowers Functional analysis Physiochemical analysis Storage life